STRATEGI KESANTUNAN POSITIF DAN NEGATIF PADA KALIMATDEKLARATIF DALAM DRAMA RICH MAN POOR WOMAN - MEIRINA, DIAH IKA (Jurnal Ilmiah Mahasiswa FIB, 2013)
This paper studies the positive and negative politeness strategy proposed by the author. The study uses qualitative description used to explain the result.  The data source is aRich Man Poor Woman of Japanese drama. The result of the study was: There were 28 declarative sentences consisted of politeness strategies to be found inRich Man Poor Woman drama. These strategies consisted of positive strategies : (1) Notice, attend to H :his interests, wants, needs, goods. (2) Exaggerate: interests, symphaty with H. (3) Intensify interest to H. (4) Avoid agreement: Token agreement, pseudo- agreement, white lies, hedging opinions. (5) Presuppose/raise/assert common ground: gossip, small talk. (6) Joke. (7) Assert or presuppose S’s knowledge of and concern for H’s wants. (8) Offer, promise. (9) Be optimistic. (10) Include both S and H in the activity. (11) Give or ask for reasons. (12) Seek agreement:safe topics, repetition.These strategies consisted of negative strategies : (1) Be pessimistic. (2) Impersonalize S and H. (3) State the FTA as a general rule. (4) Nominalize. (5) Go on record as incurring a debt, or as not indebting H. Key Word: Declarative sentence, Politeness